The Evolution of Pro-Social Behavior and the Role of the Government - Farhat, Daniel (Scientific Research, 2016)
This study explores the impact of government intervention on the evolution of cooperation using a popular framework for understanding cooperative behavior (the public goods game). Agents either contribute to the production of a shared public good or free-ride on the efforts of others. This game traditionally results in mass free-riding (a sub-optimal outcome), in which case a government can intercede by levying taxes and providing the public good to increase welfare. Is this still the case when looking at an evolutionary framework with natural selection? Theoretical results suggest that the government “levels the playing field”, allowing cooperative and uncooperative behavior to coexist longer than it ordinarily would, but it cannot change the course of evolution.
Keywords: Public Goods Game; Cooperative Behavior; Government Intervention; Evolution